2016
DOI: 10.1016/j.renene.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Testing and control of a power take-off system for an oscillating-water-column wave energy converter

Abstract: a b s t r a c tThe paper concerns the development of the PTO (power take-off) control of an OWC (oscillating-watercolumn) spar-buoy wave energy converter. The OWC spar-buoy is an axisymmetric device consisting of a submerged vertical tail tube open at both ends, rigidly fixed to a floater that moves essentially in heave. The oscillating motion of the internal free surface relative to the floater-tube set, produced by the incident waves, makes the air flow through a novel self-rectifying air turbine: the biradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(39 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…As it has been suggested, for wave energy converters, their capacity of PTO and generator will be limited for both the cost of the components and the energy conversion efficiency. Babarit et al [51] proposed that the maximal PTO power (PTO rated power) can be set to 20 times the mean annual absorbed power, and Henriques et al [52] indicated that to reduce the losses of the PTO system at partial load, the recommended generator with a rated power is twice the maximal expected average power conversion. All these have suggested that limited maximal PTO power and generator must be applied for practical purposes.…”
Section: Discussionmentioning
confidence: 99%
“…As it has been suggested, for wave energy converters, their capacity of PTO and generator will be limited for both the cost of the components and the energy conversion efficiency. Babarit et al [51] proposed that the maximal PTO power (PTO rated power) can be set to 20 times the mean annual absorbed power, and Henriques et al [52] indicated that to reduce the losses of the PTO system at partial load, the recommended generator with a rated power is twice the maximal expected average power conversion. All these have suggested that limited maximal PTO power and generator must be applied for practical purposes.…”
Section: Discussionmentioning
confidence: 99%
“…This power law has been proposed in Falcão (2002) and adopted as a rotational speed control law in other papers (e.g. Falcão and Henriques 2014a; Falcão et al 2014b;Henriques et al 2016). The constants of the straight lines in Fig.…”
Section: Power Performancementioning
confidence: 97%
“…For example, J.C.C. Henriques et al developed a PTO control of an oscillating-water-column spar-buoy wave energy converter, and hardware-in-the-loop simulation is used in experiments to characterise the proposed control algorithms [25]; Jorgen Hals et al proposed model-predictive controller to exploit the full absorption potential of wave-energy converters; N.M. Tom et al used the Pseudo-spectral control which allows optimising the controller design to achieve the optimisation of the output power of an oscillating surge WEC. Other exploration of control strategy could be seen in [26] electrical control, adaptive control in [27], phase control in [28].…”
Section: Figure 3 Ocean Energy Technology International Patent Coopermentioning
confidence: 99%